Studies on Fungal Associates of Betula utilis D. Don - Rattan, Ajay; Joshi, Madhavi; Sagar, Anand (Indian Forester, 2017)
Betula utilis D. Don is an angiosperm which belongs to family Betulaceae. Studies were carried out to find the fungal species associated with plant tissues and rhizosphere samples of B. utilis during summer, rainy and winter seasons in Himachal Pradesh. All the samples were analysed and recorded a total of ten endophytic fungi belonging to 8 genera such as (Alternaria, Aspergillus, Fusarium, Mortierella, Penicillium, Phoma, Pythium and Trichoderma) with Aspergillus and Penicillum dominating both having 2 species each. Seven species belonging to 7 genera viz., Aspergillus, Mucor, Cladosporium, Penicillium, Mortierella, Pestalotia and Trichoderma were also isolated from the rhizosphere of B. utilis. Dominating genera were Aspergillus and Penicillium as they were found in all the seasons. A total of nineteen species of AM fungi belong to 7 genera (Acaulospora, Dentisculata, Endogone, Gigaspora, Glomus, Sclerocystis and Scutellospora) were isolated from root adhering soil samples. Among them, the genus Glomus was found dominant with 10 species.